The Presumptions of Meaning. Hamblin and Equivocation. - Fabrizio Macagno (Informal Logic, 2011)
When we use a word, we face a crucial epistemic gap: we ground our move on the fact that our interlocutor knows the meaning of the word we used, and therefore he can interpret our dialogical intention. However, how is it possible to know the other’s mind? Hamblin explained this dialogical problem advancing the idea of dialectical meaning: on his view, the use of a word is based on a set of presumptions. Building on this approach, the use of a word in a dialogue can be analyzed in terms of presumptive reasoning, while the manipulative strategies based on slanted or loaded terms or redefinitions can be conceived as forms of conflicts of presumptions. A presumptive approach to meaning can also ground different dialectical strategies to solve misunderstanding or definitional disagreements, or tactics to undermine the interlocutor’s arguments by advancing charges of equivocation.